2014
DOI: 10.1248/cpb.c14-00095
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster Analysis on the Structural Diversity of Protein Crystals, Exemplified by Human Immunodeficiency Virus Type 1 Protease

Abstract: Information on many protein crystal structures has recently become available due to developments in crystallographic techniques. Even for a single kind of protein, several and sometimes many crystal structures are available. Human immunodeficiency virus type 1 (HIV-1) protease is one of the most extensively studied viral proteins, and about six hundred crystal structures have been determined. In this work, we examined the structural diversity of HIV-1 protease, classifying crystal structures into several group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…It was found that the primary factor to distinguish the crystal structures of Hb was the space group of the crystal as shown in Table 1. This is in agreement with the results of our previous study for HIV-1 PR 16 . The major space group in the crystals of Hb is P 21 21 2, and the second one is P 1 21 1.…”
Section: Clustering Of the Protein Crystal Structures Of Hbsupporting
confidence: 94%
See 2 more Smart Citations
“…It was found that the primary factor to distinguish the crystal structures of Hb was the space group of the crystal as shown in Table 1. This is in agreement with the results of our previous study for HIV-1 PR 16 . The major space group in the crystals of Hb is P 21 21 2, and the second one is P 1 21 1.…”
Section: Clustering Of the Protein Crystal Structures Of Hbsupporting
confidence: 94%
“…In our previous study for HIV-1 PR 16 , in addition to the space group and chemical agents for crystallization, the pH condition, the resolution of X-ray diffraction, the temperature factor and the inhibitor molecules were surveyed for every cluster groups to find the influence on the separation of crystal structures. No obvious factor was identified except for the space group and the chemical agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The force field parameters were ff14SB for proteins 24) and gaff2 for the compound. 25) Atom charges of the compound were determined by the quantum chemical calculation in a similar manner to the previous works. [26][27][28] Compound 1 stayed at the catalytic site all through the simulations both for poses A and B.…”
Section: Evaluation Of Inhibitory Activitymentioning
confidence: 99%
“…Furthermore, our study suggested that the precipitating agent had a strong influence on this separation. 22,23 Fudo et al crystallized a single kind of protein with three different precipitating agents and further performed MD simulations with setting the three protein crystal structures as the initial models. 24 They suggested that the precipitating agent interacted with the protein so that the agent molecule restricted the contact sites of proteins to enhance a specific molecular packing for crystal growth.…”
Section: ■ Introductionmentioning
confidence: 99%